2021
DOI: 10.1080/03009742.2021.1946255
|View full text |Cite
|
Sign up to set email alerts
|

Complement C3d is not associated with axial spondyloarthritis and magnetic resonance imaging changes at the sacroiliac joint

Abstract: Objectives:To investigate the associations between complement C3d and inflammatory and structural changes by MRI at the sacroiliac joints in a group of patients suggestive of axial spondyloarthritis according to the Assessment of Spondyloarthritis International Society (ASAS) criteria. Methods:A cross-sectional study of patients referred to the Spine Centre of Southern Denmark due to unspecified low back pain (Spines of Southern Denmark cohort). The patients were divided into three groups: Group 1: Patients fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown complement activation to be elevated in r-axSpA patients, 25 whereas others have not. 44 Previous studies (including the latter) are, however, troubled by the expanding understanding of MRI findings, for example, the presence of changes on MRI according to ASAS 2009 criteria 45 in athletes, 46 and postpartum women, 11 which has only been acknowledged in the recent years. This might have resulted in misclassification of patients in clinical cohorts encompassing both r-axSpA and nonradiographic axSpA (nr-axSpA).…”
Section: Rmd Open Rmd Open Rmd Openmentioning
confidence: 99%
“…Previous studies have shown complement activation to be elevated in r-axSpA patients, 25 whereas others have not. 44 Previous studies (including the latter) are, however, troubled by the expanding understanding of MRI findings, for example, the presence of changes on MRI according to ASAS 2009 criteria 45 in athletes, 46 and postpartum women, 11 which has only been acknowledged in the recent years. This might have resulted in misclassification of patients in clinical cohorts encompassing both r-axSpA and nonradiographic axSpA (nr-axSpA).…”
Section: Rmd Open Rmd Open Rmd Openmentioning
confidence: 99%